2019
DOI: 10.1534/g3.119.400319
|View full text |Cite
|
Sign up to set email alerts
|

QTG-Finder: A Machine-Learning Based Algorithm To Prioritize Causal Genes of Quantitative Trait Loci in Arabidopsis and Rice

Abstract: Linkage mapping is one of the most commonly used methods to identify genetic loci that determine a trait. However, the loci identified by linkage mapping may contain hundreds of candidate genes and require a time-consuming and labor-intensive fine mapping process to find the causal gene controlling the trait. With the availability of a rich assortment of genomic and functional genomic data, it is possible to develop a computational method to facilitate faster identification of causal genes. We developed QTG-Fi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
36
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 31 publications
(37 citation statements)
references
References 68 publications
1
36
0
Order By: Relevance
“…The 4-fold cross-validation results showed that the accuracy, precision, recall, and F1-Measure of the CNN model were all >73%. Compared with the recall of 64% and 79% in Arabidopsis thaliana and Oryza sativa, respectively 53 , the prediction performance of our model was good. Although the recall in Oryza sativa was higher than in our study, the genes were only prioritized in the QTL regions, while we prioritized genes in the whole genome.…”
Section: Discussionmentioning
confidence: 81%
“…The 4-fold cross-validation results showed that the accuracy, precision, recall, and F1-Measure of the CNN model were all >73%. Compared with the recall of 64% and 79% in Arabidopsis thaliana and Oryza sativa, respectively 53 , the prediction performance of our model was good. Although the recall in Oryza sativa was higher than in our study, the genes were only prioritized in the QTL regions, while we prioritized genes in the whole genome.…”
Section: Discussionmentioning
confidence: 81%
“…To prioritize candidate genes underlying QTLs, a computational approach based on algorithms would be very helpful. In a study, researchers developed QTG-Finder, a machine learning based algorithm to prioritize candidate genes by ranking them within QTL region [58]. These studies are useful to narrow down candidate genes and such algorithms should be implemented in studies aiming to predict causal QTLs and genes for traits of interest.…”
Section: Discussionmentioning
confidence: 99%
“…The methods for cross-validation, external validation and feature importance analysis were the same as previously described (Lin et al 2019). The causal genes used for external validation were not used for training the QTG-Finder models.…”
Section: Methodsmentioning
confidence: 99%